Native American Theater: A Concise History - Sidoní López,; Hanane Belali, (Miscelánea: A Journal of English and American Studies, 2016)
This paper provides a concise and brief history of Native American theater from its beginnings in indigenous oral traditions to its consolidation in the 21st century. To start with, the essay will deal with the origins of American Indian theater in Native oral traditions through storytelling and its performance. The paper will then explore the dark period of Native American drama during the emergence of Native American writing in the 18th and 19th centuries. In like manner, the essay will deal with the emergence of contemporary Native American theater as a genre during the second part of the 20th century through the numerous and multiple Native theater companies and plays. Finally, the paper will conclude with the path towards the consolidation of contemporary indigenous theater during the new millennium and will attempt to shed light on the collections and anthologies of Native American plays, a considerable body of scholarship which has just started to gain momentum, and the promotion of the genre through different institutions, companies and festivals across the country. As will be demonstrated, although Native drama is a relatively new phenomenon in the American literary landscape, the history of its development is long, complex and still developing.